Implementasi Pendidikan Seks Terhadap Identitas Gender Anak Usia 4-6 Tahun Di TK Sejahtera - Elia Wardani; Annisa Muchtar Dabigie (LP2M STAI Al-Musaddadiyah Garut, 2026)
This study aims to determine the implementation of a sex education program on the development of gender identity in children aged 4–6 years at TK Sejahtera Karangpawitan. The method used is Classroom Action Research (CAR) with a qualitative approach. The subjects consisted of 29 children (12 in class A and 17 in class B). Data collection techniques included observation, interviews, and documentation conducted over four cycles. Assessment indicators included knowledge of body anatomy, gender identity, gender roles, and self-protection. The results showed that the sex education program provided gradually was able to improve children's understanding of gender identity. In class A, there was an increase from 25% (cycle I) to 92% (cycle IV). In class B, the increase was from 77% to 77%. The children showed better abilities in recognizing sex, physical differences, and rejecting inappropriate touch. In conclusion, sex education from an early age contributes positively to the development of children's gender identity and equips them with self-protection skills. This study provides practical implications for educators and parents to no longer consider sex education a taboo, as well as social implications in efforts to prevent sexual violence against children.Keywords: Early Childhood; Sex Education; Gender Identity